China: Surpassing the "Middle Income Trap" - Zhou, Shaojie (Contemporary China Studies, 2021)
This open access book explores one of the most fiercely debated issues in China: if and how China will surpass the middle income trap that has plagued many developing countries for years. This book gives readers a clear picture of China today and acts as a reference for other developing countries. China is facing many setbacks and experiencing an economic slowdown in recent years due to some serious issues, and income inequality is one such issue deferring China's development potential by creating a middle income trap. This book thoroughly investigates both the unpromising factors and favorable conditions for China to overcome the trap. It illustrates that traps may be encountered at any stage of development and argues that political stability is the prerequisite to creating a favorable environment for economic development and addressing this "middle income trap". Written by one of China's central planners, this book offers precious insights into the industrial policies that are transforming China and the world and will be of interest to China scholars, economists and political scientists.